Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function - Gail Davies (Nature Portfolio, 2018)
Cognitive function is associated with health and important life outcomes. Here, the authors perform a genome-wide association study for general cognitive function in 300,486 individuals and identify genetic loci that implicate neural and cell developmental pathways in this trait.